The Influence Of Personality On Job Satisfaction Of The Head Of Bumdesa In The Bogor District - Herman Herman; May Mulyaningsih; Sri Hartini (Universitas Dharma Wacana, 2022)
The purpose of this study is to determine the influence of personality on job satisfaction Head of BUM Villages in Bogor Regency, using a questionnaire that has been tested for validity and reliability by as many as 30 respondents from 131 people, with the verification method carried out through the method and analysis of the Structural Equation Model (SEM) equation using the Lisrel 8.70 software. Based on the results of data analysis, the value of t-count < t-table, or 11.88 > 1.96. The significance test was carried out by t-test at the level of = 0.05 and obtained a t-count value of 11.88 and more excellent than 1.96. Thus H0 is rejected, and H1 is accepted; this means that the hypothesis that personality has a significant effect on job satisfaction. This means that personality variables have a significant influence on job satisfaction. Based on these results, to improve the personality of the BUMDes head in Bogor Regency, the recommended program is to increase the dimension of openness to experience with indicators of fantasy, aesthetics, feelings, actions, ideas, and values. Another program that can be implemented is through training on the formation of characteristics, aesthetics, and the formation of individual values for the heads of BUMDes in Bogor Regency. The suggested program is to increase the dimension of openness to experience with indicators of fantasy, aesthetics, feelings, actions, ideas, and values. Programs can be implemented through increasing responsibility for actions/activities and generating business ideas.